2020
DOI: 10.1002/adhm.202001208
|View full text |Cite
|
Sign up to set email alerts
|

Thermo‐Triggered In Situ Chitosan‐Based Gelation System for Repeated and Enhanced Sonodynamic Therapy Post a Single Injection

Abstract: Sonodynamic therapy (SDT) by utilizing ultrasonic waves triggers the generation of reactive oxygen species (ROS) with the help of sonosensitizers to destruct deep‐seated tumors has attracted great attention. However, the efficacy of SDT may not be robust enough due to the insufficient oxygen supply within solid tumors. Additionally, repeated injections and treatments, which are often required to achieve the optimal therapeutic responses, may cause additional side effects and patient incompliance. Herein, a the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 53 publications
(41 reference statements)
0
20
0
Order By: Relevance
“…Under ultrasound, local TCPP–CAT generates ROS and promotes the efficacy of SDT in tumor killing by triggering the decomposition of endogenous H 2 O 2 to produce O 2 , which in turn continuously improves the hypoxic tumor microenvironment. 78 In a later study, a similar novel polymeric nano-drug delivery material was designed by Li et al , who developed a transmucosal oxygen self-producing SDT nanoplatform to achieve high-efficiency SDT targeting BCa ( Fig. 4D ).…”
Section: Application Of Sonosensitizers In Sdtmentioning
confidence: 99%
“…Under ultrasound, local TCPP–CAT generates ROS and promotes the efficacy of SDT in tumor killing by triggering the decomposition of endogenous H 2 O 2 to produce O 2 , which in turn continuously improves the hypoxic tumor microenvironment. 78 In a later study, a similar novel polymeric nano-drug delivery material was designed by Li et al , who developed a transmucosal oxygen self-producing SDT nanoplatform to achieve high-efficiency SDT targeting BCa ( Fig. 4D ).…”
Section: Application Of Sonosensitizers In Sdtmentioning
confidence: 99%
“…In localized tumor therapy, US modifies the implanted platform structurally to allow drug release or increases cargo release directly through diffusion. 105,106 Meng et al developed a hydrogel system that responds to US for the delivery of nanovaccines against breast cancers in a study. 105 In the suggested personalized immunotherapy strategy, ultrasonic irradiation caused a gel-to-sol change, resulting in the release of the vaccine.…”
Section: Advantages Of Ultrasound-responsive Implantable Hydrogel-bas...mentioning
confidence: 99%
“…According to She et al's design, hydrogel development was induced in situ at the temperature of the human body. 106 The precursor solution contained catalase coupled with the sonosensitizer meso-tetra (4-carboxyphenyl) porphine (TCPP), beta-glycerol phosphate disodium (GP), and chitosan. Catalase's presence relieved the solid tumor's hypoxic status and improved SDT efficacy.…”
Section: Advantages Of Ultrasound-responsive Implantable Hydrogel-bas...mentioning
confidence: 99%
“…Although recent research studies have demonstrated that photodynamic therapy (PDT) is a noninvasive therapeutic method with very promising therapeutic benefits for cancer therapy, the clinical applications of PDT are very limited due to the limited tissue penetration depth of light (the maximum tissue penetration rate of light is only millimeters). Similarly, ultrasound (US) also can trigger the reactive oxygen species (ROS) generation to kill cancer cells in the presence of sonosensitizers. Unlike light, US, a periodically vibrating mechanical wave, , has shown much higher tissue penetration depth (more than 10 cm in soft tissues) and is very promising for noninvasive therapy against tumors. However, clinical trials of sonodynamic therapy (SDT) are still pending due to several limitations, primarily the low efficiency of sonosensitizers, low retention of sonosensitizers in cancer cells, , and low cancer selectivity. Hence, to achieve good therapeutic effects, repeated administration of therapeutic agents by systemic injection is often required, which results in exacerbation of side effects and reduces patient compliance. , Generally, the aggregation/assembly-induced retention (AIR) effect in cancer cells can significantly enhance the retention of bioactive molecules at disease sites, which increases the sensitivity and cancer-selectivity and shortens the US time. However, the AIR effect is based on supramolecular weak interactions, such as π–π interactions, hydrogen bonding, etc, which can be easily broken by US; moreover, the construction of controllable sonosensitizer building blocks with bifunctional groups and predictable in vivo self-assembly behavior still faces obstacles.…”
Section: Introductionmentioning
confidence: 99%